2019
DOI: 10.3390/nu11122861
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Sarcopenia in Older Persons

Abstract: Vitamin D deficiency is a common health problem worldwide, in particular among older people. Vitamin D regulates and modulates the physiology and function of multiple human systems, including the skeletal muscle. The effect of vitamin D on the muscle has been widely investigated, suggesting that this hormone can stimulate the proliferation and differentiation of skeletal muscle fibers, maintaining and improving muscle strength and physical performance. Older persons have a higher prevalence of low Vitamin D le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
3
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(208 citation statements)
references
References 76 publications
4
154
3
7
Order By: Relevance
“…It has recently been proven that deficiency or insufficiency in vitamin D is positively correlated with the risk of several diseases including sarcopenia, cardiovascular diseases, obesity, and cancer. Indeed, Remelli et al reviewed the biological, clinical and epidemiological evidence supporting the association between vitamin D and an increased risk of sarcopenia in older people [ 15 ]. Consequently, attention has been drawn to the other aspects of vitamin D metabolism other than Ca 2+ homeostasis.…”
Section: Vitamin Dmentioning
confidence: 99%
“…It has recently been proven that deficiency or insufficiency in vitamin D is positively correlated with the risk of several diseases including sarcopenia, cardiovascular diseases, obesity, and cancer. Indeed, Remelli et al reviewed the biological, clinical and epidemiological evidence supporting the association between vitamin D and an increased risk of sarcopenia in older people [ 15 ]. Consequently, attention has been drawn to the other aspects of vitamin D metabolism other than Ca 2+ homeostasis.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Additionally, age-related musculoskeletal declines such as osteoporosis and sarcopenia are directly related to aging and can catalyze frailty in older populations. Of particular interest are the contributions of sarcopenia, the loss of muscle mass and function over time, to the frailty phenotype [ 7 ]—especially in light of the important role vitamin D appears to play in the development of sarcopenia [ 8 ]. Furthermore, we have previously published that chronic vitamin D insufficiency in middle-aged mice induces physical performance decline in grip endurance and anaerobic performance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Putting these in perspective, vitamin D has both positive and negative effects on myogenic cells; hence, vitamin D treatment should probably be used for the prevention of age-related muscle loss rather than for sarcopenia treatment. However, a number of clinical studies demonstrated an improvement of muscle strength in vitamin D-treated elderlies, suggesting that vitamin D supplementation is an effective therapeutic approach for sarcopenia [43]. In this study, we did not perform the functional study to clarify the vitamin D's action on muscle strength.…”
Section: Discussionmentioning
confidence: 90%